2008
DOI: 10.1080/14786410701389159
|View full text |Cite
|
Sign up to set email alerts
|

Sesquiterpenoid alkaloid fromAcroptilon repens

Abstract: One new sesquiterpenoid alkaloid, namely 3 beta,8 alpha-dihydroxy-13-pyrrolidine-4(15),10(14)-(1 alpha H,5 alpha H,6 beta H,11 beta H)-guaiadien-12,6-olide (1), together with two known guaiane-type sesquiternoids (2-3) was isolated from the aerial part of Acroptilon repens. The structure of 1 was established by spectroscopic methods, especially 2D NMR (HMQC, HMBC, and NOESY). Cytotoxic activity against tumor cell line was assessed for compounds 2-3, and found to show potent cytotoxic activities against tumor c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 12 publications
1
4
0
Order By: Relevance
“…Our findings showed that lipid peroxidation, protein carbonyl, and ROS contents significantly increased but CAT and SOD levels decreased in the liver and brain of mice treated with extract (500 and 1000 mg/kg) for 28 days. Due to hypoxic potentials of A. repens's extract [8], the results presented in this study further verify that extract administration-induced oxidative stress could occur along with an increase in the oxidation products and decreased in the activities of antioxidant enzymes.…”
Section: Discussionsupporting
confidence: 72%
See 3 more Smart Citations
“…Our findings showed that lipid peroxidation, protein carbonyl, and ROS contents significantly increased but CAT and SOD levels decreased in the liver and brain of mice treated with extract (500 and 1000 mg/kg) for 28 days. Due to hypoxic potentials of A. repens's extract [8], the results presented in this study further verify that extract administration-induced oxidative stress could occur along with an increase in the oxidation products and decreased in the activities of antioxidant enzymes.…”
Section: Discussionsupporting
confidence: 72%
“…Zhan et al. reported that a new sesquiterpenoid compound from A. repens's extract showed a potent cytotoxic activities on the tissue culture through hypoxic mechanism [ 8 ]. Also, acute hypoxia has been shown to increase the production of ROS in the cell by changing the activity of cytochrome chains, which are responsible for the oxidative phosphorylation of mitochondria [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Compounds 149 and 162 showed very potent cytotoxic activity against tumor cell line P388 (murine leukemia), more than the natural anticancer agent pseudolaric acid B used as positive control, at the IC 50 levels of 0.36 and 0.01 lM, respectively (Zha and Hou, 2008). They were also tested against human cancer cell lines of malignant melanoma (SK-MEL), epidermoid (KB), ductal (BT-549) and ovarian (SK-OV-3) carcinomas for cynaropicrin (162), janerin (208) and chlorojanerin (219), showing in vitro cytotoxic activity with IC 50 values of 2-6 lg/mL (Muhammad et al, 2003).…”
Section: Antitumor and Cytotoxicmentioning
confidence: 99%